2019
DOI: 10.1186/s12879-019-3901-y
|View full text |Cite
|
Sign up to set email alerts
|

A population-based analysis of invasive fungal disease in haematology-oncology patients using data linkage of state-wide registries and administrative databases: 2005 - 2016

Abstract: BackgroundLittle is known about the morbidity and mortality of invasive fungal disease (IFD) at a population level. The aim of this study was to determine the incidence, trends and outcomes of IFD in all haematology-oncology patients by linking Victorian hospital data to state-based registries.MethodsEpisodes of IFD complicating adult haematological malignancy (HM) and haematopoietic stem cell transplantation (HSCT) patients admitted to Victorian hospitals from 1st July 2005 to 30th June 2016 were extracted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 42 publications
1
20
0
3
Order By: Relevance
“…Over the six‐year study period, total attributable hospitalisation costs were stable ( P = .90) with increases in IA ( P = .63) and other IFD ( P = .88) balanced against a decrease in invasive candidiasis related costs ( P = .08) with none reaching statistical significance likely due to small numbers of matched pairs. A 0.28% decrease in IFD incidence in the companion epidemiological study corroborates institutional studies from two major Victorian transplant centres suggesting that improvements in supportive care like antifungal prophylaxis have affected IFD incidence.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Over the six‐year study period, total attributable hospitalisation costs were stable ( P = .90) with increases in IA ( P = .63) and other IFD ( P = .88) balanced against a decrease in invasive candidiasis related costs ( P = .08) with none reaching statistical significance likely due to small numbers of matched pairs. A 0.28% decrease in IFD incidence in the companion epidemiological study corroborates institutional studies from two major Victorian transplant centres suggesting that improvements in supportive care like antifungal prophylaxis have affected IFD incidence.…”
Section: Discussionsupporting
confidence: 74%
“…The implications of our findings underscore the importance of ALL as a HM subgroup associated with high IFD treatment‐related costs. Further, Valentine et al demonstrated that the prevalence of IFD in ALL patients is high (11%) as compared to AML (9.42%) and auto‐HSCT (4.83%) patients. These data are a compelling argument for better preventative strategies including mould‐active antifungal prophylaxis that are as yet unresolved in patients with ALL …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Australian infectious diseases cohort studies have involved: organ specific infections such as respiratory viral infections, 13 infections such as Q fever 12 and S. aureus bacteraemia 14 as well as specific patients such as asplenics 16 and haematology-oncology. 17 The value of Australian patient cohorts for infectious diseases research is further shown by the multiple studies deriving from the 45 and up study of ageing, 18 Triple I Western Australian birth cohort 15 and Victorian Post-Splenectomy Registry. 19 There are inherent limitations of retrospective databases defined by ICD-10-AM codes.…”
Section: Discussionmentioning
confidence: 99%
“…However, these are complex and require detailed case review. Administrative coding data possess potentially favourable attributes for simplified surveillance [9], including standardised classification and availability of specific codes for yeast and mould infections [4,10]. In Australia, the International Statistical Classification of Diseases and Related Health Problems, Tenth Revision, Australian Modification (ICD-10-AM) are a monohierarchical, codified, medical lexicon used for coding inpatient diagnoses and is a commonly used ontology to inform activity-based funding models [11].…”
Section: Introductionmentioning
confidence: 99%